2010
DOI: 10.1002/ls.123
|View full text |Cite
|
Sign up to set email alerts
|

Friction evaluation of lubricated laser‐textured surfaces

Abstract: Despite a large amount of work dedicated to the study of the effects of textured surfaces in tribological pairs, there is still a need for accurate and convincing experimental results to prove the benefi c effects predicted theoretically. This paper presents an original experimental set-up with a partially textured fl at pin sliding on a rotating disc in the presence of a thin lubricating fi lm of constant thickness. The texture was composed of a series of parallel grooves cut on the half of the pin front face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…Thus, the additive load and viscosity requirements of the lubricant can be reduced, while achieving sufficient film thickness to keep friction low. In addition, the lubricant enters the dimples and produces a local hydrodynamic wedge effect . Another function of surface textures is that of trapping detached metal particles and impurities in general .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the additive load and viscosity requirements of the lubricant can be reduced, while achieving sufficient film thickness to keep friction low. In addition, the lubricant enters the dimples and produces a local hydrodynamic wedge effect . Another function of surface textures is that of trapping detached metal particles and impurities in general .…”
Section: Introductionmentioning
confidence: 99%
“…These forces are almost equal in absolute value with those from the corresponding case of direct motion. The minimum film pressure calculated from the measured normal force using equation (4) was as low as 0.027 MPa in absolute.…”
Section: Starved Lubricationmentioning
confidence: 87%
“…A large amount of work have been carried out to predict pavement friction from texture measurements using experimental methods (Leu et al, 1978;Yandell et al, 1983;Purushothaman et al, 1990;Do et al, 2004;Alvarez et al, 2005;Ergu et al, 2005;Kebrle et al, 2007, Predescu et al, 2010, but with limited successes. Studies indicated pavement texture is not the only factor influencing pavement friction, instead the predicative capability of models depends on a multitude of factors such as tire inflation pressure, temperature, rubber wear or aging, sliding velocity, vertical load, pavement texture property, and even road evenness and curviness (Klüppel et al, 2000;Persson, 2001).…”
Section: Introductionmentioning
confidence: 99%